Vicky Foskolou & Sophia Kalopissi-Verti (eds.), Intercultural Encounters in Medieval Greece after 1204. The Evidence of Art and Material Culture - CAILLET, Jean-Pierre (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2023)
Vicky Foskolou & Sophia Kalopissi-Verti (eds.), Intercultural Encounters in Medieval Greece after 1204. The Evidence of Art and Material Culture (BYZANTIOς. Studies in Byzantine History and Civilization 19), Brepols Publishers n.v, Turnhout, Belgium 2022. 572 p. avec 220 illustrations noir-blanc dans le texte, et XXXV planches couleurs hors-texte. 15,6×23,4 cm. ISBN: 978-2-503-59850-5, eISBN: 978-2-503-59851-2.